A function for the pleurogram in physically dormant seeds. (15th December 2018) - Rodrigues-Junior, Ailton G; Mello, Ana Caroline M P; Baskin, Carol C; Baskin, Jerry M; Oliveira, Denise M T; Garcia, Queila S
Abstract: Background and Aims: Different structures have been shown to act as a water gap in seeds with physical dormancy (PY), and in Fabaceae they are commonly located in the hilar region. However, the function of the pleurogram, a structure in the extra-hilar region that is common in legume seeds, remains unknown. Our aims were to review the literature for occurrence of the pleurogram in Fabaceae, determine if the pleurogram can open, and compare the functional morpho-anatomy of water gaps in seeds of 11 Senna species. Methods: Imbibition tests showed that all 11 species had PY. Structural features of the hilar and extra-hilar regions of the seeds were investigated using light and scanning electron microscopy, and dye-tracking was performed to trace the pathways of water through the seed coat. Key Results: A pleurogram has been reported for 37 legume genera. Water gaps differed among Senna species, with lens, hilum, micropyle and pleurogram taking up water after PY was broken. In Senna alata seeds, only the pleurogram acted as a water gap, whereas in S. reniformis and S. silvestris water entered the seed through both the pleurogram and the hilar region. In the pleurogram of S. alata and S. reniformis, the palisade layer moved outward, exposing the hourglass cells, whereas in S. silvestris the palisade layer was broken. Conclusions: The pleurogram acts as a water gap in some of the 11 Senna species examined, but it is non-functional in others. Opening the pleurogram occurs due to the formation of a linear slit in the palisade layer. The pleurogram is of functional significance by creating a wide opening, whereby water can reach the embryo and start germination. This is the first report of the pleurogram functioning as a water gap. Because this structure is shared by at least 37 genera, it also may be a water gap in many other legume species.